Prevalence of Nocturnal Enuresis in School-age Children in Rafsanjan - Torkashvand, Fatemeh; Rezaeian, Mohsen; Bagheani, Tahereh; Abdolkarimi Dawarani, Mohammad ali; Zarafshan, Hadi; Mostafavi, Seyed-Ali; Bidaki, Reza (Journal of Pediatric Nephrology, 2015)
Introduction: Nocturnal enuresis is an important developmental problem for school age children and it can cause emotional and social problems for children and their families. This study was aimed to determine the prevalence of enuresis in school children aged 6-8 years in Rafsanjan, Iran, during 2014. Material and Methods: In this cross-sectional study, 1080 school children aged 6-8 were selected using a random cluster sampling method. Questionnaires were distributed among the children to be answered by their parents. Results: The overall prevalence of nocturnal enuresis was10.6% (CI 95%: 8.76 – 12.44); 91.3 % of them had primary and 8.7% had secondary nocturnal enuresis. Prevalence in girls and boys were 8.44% and 12.3% respectively. Factors such as parental education, family income, and age were significantly associated with nocturnal enuresis. Conclusions: The results showed that the prevalence of nocturnal enuresis in our study is average. Since a minority of families seek medical advice and treatment for their children, family education and awareness is essential in this regard. Keywords: Nocturnal enuresis, Child, Prevalence, Schools